ISOLASI DAN KARAKTERISTIK BAKTERI LIMBAH CAIR MINYAK BUMI DI PERTAMINA KECAMATAN LIRIK SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK BIOLOGI SMA - Alfi Rahmah; Irda Sayuti; Devi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to determine the characteristics of petroleum liquid waste bacteria in pertamina company at Lirik district which was used in designing student worksheets in the X class kingdom monera material of high school conducted in December 2018 to January 2019. This research is descriptive and conducted by examination in the laboratory. The sampling technique in this study done by using purposive sampling method. The parameters used include bacterial characteristics through macroscopic observations, namely the form of colonies, colony color, colony edge and colony elevation, then microscopic observations namely gram staining. The results showed that bacteria found to have white and yellow characteristics. Forms of colonies found were irregular, circular and rhizoid. The edge of the colony found is serrate, lobate and entire. The elevation of bacteria found is raised and flat. The most commonly found bacterial cell form is coccus, while gram-positive bacteria are the most common bacteria. The results of this study were further developed into the design of designing student worksheets material in class X high school kingdom moneraKey Words: Characteristics, Macroscopic, Microscopic, Isolate, Student Worksheets